ANALISIS PROSES SUKSESI DAN TANTANGAN GENERASI KEDUA DI PT ALFA VIKTORI FAMILIA - Sofia Umari; Metta Padmalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study analyzes the succession process and challenges faced by the second generation in PT Alfa Viktori Familia, a family-owned company in Indonesia. This study uses a qualitative approach with in-depth interview methods with the main informant sources, namely the founder as the first and second generation successor, managerial staff, and experts in the family business. The research results show that commitment and trust are factors in the succession process, with family values ​​having a big role and also helping in shaping the successor's readiness to continue the business. The analytical framework uses the Seven-Pointed Star Model by Rothwell, which covers seven aspects of succession planning. The research results show that aspects of intergenerational commitment and trust have been implemented strongly. However, most other aspects such as assessing potential successors and development programs have not been carried out systematically. The challenges faced include difference in leadership styles, adaptation to technological and market changes, and gaps between generations. This study suggests the need for a more professional succession system, including the use of performance indicators (KPI), mentoring programs, and ongoing evaluation to ensure business continuity across generations. These findings contribute to the business literature and become a practical reference for family companies in Indonesia.